Corporate financial performance and Tobin's q in dividend and growth investing - Hanna Mysaka; Ivan Derun (Contemporary Economics, 2021)
Investor attracting and keeping requires both successful management of a company's financial performance and an investor's behavior knowledge, as well as monitoring of stock market current trends. This paper contains the study results on the influence of public companies' financial performance on Tobin's q as a common measure of investment opportunity for dividend (income) investors and growth investors in conditions of competition and financing limitations. The goal of this article is to identify the financial performance indicators of public companies, influencing their Tobin's q, for dividend (income) investing and growth investing respectively. We determined that the proxies for the variables of the Tobin's q function should be different for different investment styles. For this reason, we composed two sets of financial ratios that reflect financial performance specifics of dividend (income) stock companies and growth stock companies for the quantitative assessment of these investor types' preferences. The analysis results led to the conclusion that a company can attract attention of dividend (income) investors by demonstrating higher levels of dividend payments. Whereas, growth investors are sensitive to the level of company's business activities, which is related to its revenue. Based on the results of this study, we believe that investment decisions' successfulness depends on the reliability of the issuer's financial statements. In our conclusions, we suggest that public companies' managers focus on the financial performance that best correlate with the preferences of certain type of investors, which is a promising way to attract and keep their investors.
Keywords: G32; M41; G11; 330; Dividend (income) investors; financial performance; growth investors; Tobin's q